1995
DOI: 10.1143/jjap.34.l455
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide-Loaded Tin Dioxide Thin Film for Detection of Dilute Hydrogen Sulfide

Abstract: The H2S sensing characteristics of SnO2 thin films loaded with CuO were found to be much improved by reducing the film thickness. A 40-nm-thick film showed sensitivity as high as 20000 and 2000 to 1.5 and 0.3 ppm H 2 S in air, respectively, at 200° C, while the rate of response to 0.3 ppm H 2 S was rather slow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The p-n heterocontact concept is used in the present investigation, instead of adsorption-desorption mechanism, which was introduced in 1979 and has been applied as humidity sensors, liquid sensors and gas sensors [27][28][29][30][31][32][33][34]. The heterocontact concept was found to be very effective for the H 2 S gas sensing at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The p-n heterocontact concept is used in the present investigation, instead of adsorption-desorption mechanism, which was introduced in 1979 and has been applied as humidity sensors, liquid sensors and gas sensors [27][28][29][30][31][32][33][34]. The heterocontact concept was found to be very effective for the H 2 S gas sensing at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the detection of dilute H 2 S less than 1 ppm, thin film or thick film sensors using CuO-SnO 2 [5,6], WO 3 [7][8][9], and CuO-doped SnO 2 [10] have been reported to show excellent performance. Recently, nanophased WO 3 -based H 2 S gas sensors have been reported [11] for the detection of ppb-level H 2 S. It is reported that CuO-surface modified BSST (using dipping technique) sensors respond to 100 ppm H 2 S gas at 300 • C. Instead of such modification of the film surface, BSST was doped with CuO in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The p-n heterocontact concept was used in the present investigation [18][19][20][21][22][23][24][25][26][27]. There is an intrinsic difference in the behavior between the heterocontact type sensors and the sensors based on catalytic oxidation/reduction of gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Sintered pastes [5], thick [6], and thin-film structures using mixed -powders, Cubilayers [7], and -hetero-contacts [8], chemically-fixed on [9], [10] have been extensively investigated. Some of those sensor materials offer a high sensitivity but response time is often found to be slow (3 to 175 min) [2]- [5], [8], [11]- [13] and a faster response time (15 to 180 s) has been reported only for a higher concentrations of gas [6], [7], [9], [10]. The high sensitivity of -doped sensors has been attributed to the electronic interaction between the -type and the -type polycrystalline [14] and the effect of gas in reducing the barrier height [15].…”
Section: Introductionmentioning
confidence: 99%